1966
DOI: 10.1071/bi9660673
|View full text |Cite
|
Sign up to set email alerts
|

Histological Observations on the Reproductive Tract of the Ewe

Abstract: SummaryAn histological examination of the female reproductive tract showed that all parts of the tract undergo cyclical changes. In general the height of the lumenal epithelium reaches a maximum during oestrus and secretory activity also appears to be maximal at this time.Secretory cells were not seen in the vagina. The cervix, however, had an epithelium continually containing mucus-secreting cells. This mucus was released into the cervical lumen during pro-oestrus and oestrus. The glands of the uterus exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

1968
1968
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 5 publications
(14 reference statements)
2
21
1
Order By: Relevance
“…There was no difference on the histological samples obtained from ewes that came into oestrus or not. Although the histological pattern of the animals that came into oestrus was similar to that observed during a normal oestrous cycle, those that did not come into oestrus and were sampled 72 h after IS withdrawal also had inflammatory characteristics (Restall ). In that sense, Restall () reported that the vaginal epithelium shows an increase in the thickness of the epithelium occurring during oestrus, followed by keratinization and desquamation.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…There was no difference on the histological samples obtained from ewes that came into oestrus or not. Although the histological pattern of the animals that came into oestrus was similar to that observed during a normal oestrous cycle, those that did not come into oestrus and were sampled 72 h after IS withdrawal also had inflammatory characteristics (Restall ). In that sense, Restall () reported that the vaginal epithelium shows an increase in the thickness of the epithelium occurring during oestrus, followed by keratinization and desquamation.…”
Section: Discussionmentioning
confidence: 76%
“…Although the histological pattern of the animals that came into oestrus was similar to that observed during a normal oestrous cycle, those that did not come into oestrus and were sampled 72 h after IS withdrawal also had inflammatory characteristics (Restall ). In that sense, Restall () reported that the vaginal epithelium shows an increase in the thickness of the epithelium occurring during oestrus, followed by keratinization and desquamation. The similarity between these two groups (came into oestrus or not) confirms that the pattern observed even 72 h after IS withdrawal is a consequence of the conditions generated by the treatment, and not just by the hormonal changes that occurred later.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…But evidence from studies in vivo and in vitro suggests strongly that the secretions essential for the fertilization and early development of the egg are furnished by the ampulla rather than the isthmus, the former having been shown in a number of species to be the most active secretory region of the entire oviduct (e.g. for the ewe: Hadek, 1955;Restall, 1966;Restall & Wales, 1968). Furthermore, Whittingham (1968) has reported that mouse zygotes degenerated when cultured within the explanted isthmus, whereas the explanted ampullar region of the tube was able to support develop¬ ment, and he commented that the paucity or absence of secretory cells in the mouse isthmus could explain this situation.…”
Section: Discussionmentioning
confidence: 99%
“…The fallopian tube also shows morphological differences along its length, the secretory cells being mainly contained in the ampulla region (Hadek 1955;Restall 1966c). The epithelia of the isthmus and ampulla also appear to respond differently to oestrogen (Restall 1966b).…”
Section: Introductionmentioning
confidence: 99%